Preaching in the Context of Pluralistic Society from the Perspectiveof Reformed Theology - Hyun-Jong Jung (Sekolah Tinggi Teologi Abdiel, 2026)
Plurality is an undeniable empirical reality, especially in the Indonesian context. This reality poses a challenge for preachers. The questions that must be answered are: how should a preacher convey biblical truth in the context of this pluralistic society? How should preachers proclaim the Gospel? What is the perspective of Reformed theology on this matter? This research uses a literature review method, in which I will explore sources related to the themes discussed above. The books and articles I utilize are largely part of Reformed theology, in order to gain sufficient insight into Reformed theology's perspective on this issue. The conclusions of this research clearly illustrate that in delivering a biblical sermon, a preacher must pay close attention to the method of exploring the Bible correctly and responsibly. In accordance with Reformed theology's belief,